2014
DOI: 10.1007/s12282-014-0545-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of prone-to-supine tumor displacement in the breast using patient position change: investigation with prone MRI and supine CT

Abstract: The present study showed that prone-to-supine tumor displacement in the breast differs depending on tumor location. The inner-lower quadrant of the breast may be the most predictable area for prone-to-supine tumor displacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Although the examination was performed on the same patient in both the prone and supine positions, we did not include an estimate of the spatial displacement of the lesions in our objectives. Indeed, although it might seem easy to estimate the displacement of the breast lesions by changing from the prone to the supine position, on the contrary, the models proposed and published to date [ 31 , 32 , 33 ] have not considered the same examination technique in the transition to the supine position, or have made only one assessment of the displacement. We believe that the results would have been statistically more consistent if the measurements had been repeated several times so as to assess the error in the estimate of the lesion position.…”
Section: Discussionmentioning
confidence: 99%
“…Although the examination was performed on the same patient in both the prone and supine positions, we did not include an estimate of the spatial displacement of the lesions in our objectives. Indeed, although it might seem easy to estimate the displacement of the breast lesions by changing from the prone to the supine position, on the contrary, the models proposed and published to date [ 31 , 32 , 33 ] have not considered the same examination technique in the transition to the supine position, or have made only one assessment of the displacement. We believe that the results would have been statistically more consistent if the measurements had been repeated several times so as to assess the error in the estimate of the lesion position.…”
Section: Discussionmentioning
confidence: 99%
“…Telegrafo et al 4 showed that a key issue for clinical use of pre-operative breast MRI is how to transfer the three-dimensional (3D) information obtained from the patient in prone position to the operating room, since the surgical treatment is performed in the supine position 4,10 . If the location of MRI-detected tumors in the supine position could be predicted, those predicted positions could be used as a surgical planning guide for the surgeon 11,12 , which could then promote a decrease in the re-excision rate of BCS.…”
mentioning
confidence: 99%
“…To address this shortcoming, the distance of the tumors from the chest wall should be measured and compared to those at the nipple origin. The study by Satake et al 11 assessed the prediction of prone-to-supine tumor movement in the breast considering movement direction. However, only movement in the coronal plane was analyzed, which cannot show the movement of the tumor in three-dimensional (3D) coordinates.…”
mentioning
confidence: 99%
“…Actually, the shape of the breast is quite different between the prone position required during MRI scans and in a supine position on the operating table. Therefore, the location and spread of breast cancers must change from the time of MRI scans to the OR [6,7]. It requires labor and experience for breast surgeons to reconstruct the spread of breast cancer and to determine the optimal surgical line from MRI.…”
Section: Introductionmentioning
confidence: 99%